High prevalence of non-alcoholic fatty liver disease in patients with a first episode of acute ischemic stroke. Impact on disability and death - Canillas, Lidia; Soriano-Varela, Agnes; Rodríguez-Campello, Ana; Giralt-Steinhauer, Eva; Cuadrado-Godia, Elisa; Broquetas, Teresa (Frontiers in Endocrinology, 2022)
Introduction Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, and it is associated with an increased risk of overall mortality being cardiovascular disease the most common cause of mortality. Strategies are needed to identify high risk groups for NAFLD to improve screening approaches. Moreover, there is a lack of information about the prevalence of NAFLD on patients with acute ischemic stroke (AIS) and the influence of NAFLD on the prognosis of the stroke. The aim of the study was to define the prevalence of NAFLD in patients with a first episode of AIS and the secondary aims were to evaluate the prevalence of NAFLD at different ages and its impact on the severity and prognosis of the AIS. Materials and methods Observational study including consecutive patients admitted for the first AIS from January 2005 to May 2018. Patients with harmful alcohol intake, other liver diseases and malignancies were excluded. Sociodemographic data, cardiovascular risk factors, comorbidities, and blood test at admission were reviewed. NAFLD and liver fibrosis were assessed with the serological scores Fatty Liver Index (FLI) and Fibrosis-4 respectively. NAFLD was defined by a FLI>60. Stroke severity and prognosis were evaluated with the National Institute of Health Stroke Scale and modified Rankin Scale respectively in patients aged from 40 to 79 years old. Results We included 1601 patients, 52.4% were female and median (IQR) age of 77 (66 – 83) years. The 41% of the total cohort had a FLI>60 with different prevalence according to age in decades: in 30-39 years: 35.7%; in 40-49: 47.5%; in 50-59: 51.1%, in 60-69: 56%, in 70-79: 41.4%; in 80-89: 34.9% (p<0.001). The presence of NAFLD did not impact on the severity or the prognosis of stroke. However, patients with NAFLD were younger than those without NAFLD (74 vs. 78; p<0.001). Conclusion Presence of NAFLD did not impact on disability and death after the stroke. However, patients with a first episode of stroke showed a high prevalence of NAFLD, especially at intermediate ages, and therefore, screening for NAFLD should be advisable.